The Potential Effect of Plant Based Antioxidants in Breast Cancer Prevention and Treatment - Shi, Chaojia; Fang, Gang; Song, Huanhuan; Qin, Xinyuan; Liu, Yueting; Luo, Yuxuan; Li, Wenhui; Cao, Zhiyong; Li, Jingjing; Fan, Xiaoting (Indian Journal of Pharmaceutical Education and Research, 2026)
ABSTRACT Breast cancer is the most common cause of death among women worldwide. According to the 2024 Cancer Statistics report, it has surpassed lung cancer as the most frequently diagnosed cancer around the world. Oxidative stress is one of the most common risk factors for breast cancer. Oxidative stress can cause mutations in breast tissue that can ultimately lead to breast cancer. Antioxidants are molecules that nullify the effects of oxidative damage and can be used as chemopreventive and chemotherapeutic agents for breast cancer. The present review examines natural antioxidants, such as vitamins, curcumin and quercetin and their roles as chemopreventive and anticancer agents for breast cancer. Many in vitro and in vivo studies support their effects as chemopreventive or chemotherapeutic agents. Although many additional studies are required to support their use as drugs, in the future, these molecules are potential candidates for chemopreventive and chemotherapeutic drugs against breast cancer.
Keywords: Antioxidants; Breast cancer; Oxidative stress; Free radicals; Chemoprevention; Chemotherapy.